2013
DOI: 10.3109/01942638.2012.747582
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Standing and Sitting Postures of Youth with Idiopathic Scoliosis from Quantitative Analysis of Digital Photographs

Abstract: The objective of this study was to explore whether differences in standing and sitting postures of youth with idiopathic scoliosis could be detected from quantitative analysis of digital photographs. Standing and sitting postures of 50 participants aged 10–20-years-old with idiopathic scoliosis (Cobb angle: 15° to 60°) were assessed from digital photographs using a posture evaluation software program. Based on the XY coordinates of markers, 13 angular and linear posture indices were calculated in both position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…In previous photographic studies, the distance between the camera and the object was reported to be 173 cm [97, 100], 300 cm [73, 81, 95, 101], or 400 cm [55]. The camera was positioned at the height of 70, 127, 80 or 90 cm [81], while other authors set the camera by centering the lens at half of the child’s height [81, 95, 98].…”
Section: Discussionmentioning
confidence: 99%
“…In previous photographic studies, the distance between the camera and the object was reported to be 173 cm [97, 100], 300 cm [73, 81, 95, 101], or 400 cm [55]. The camera was positioned at the height of 70, 127, 80 or 90 cm [81], while other authors set the camera by centering the lens at half of the child’s height [81, 95, 98].…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot determine the error of measurement related to patient position. Fortin et al found significant reliability of a photography technique similar to that used in our investigation [29,30]. To diminish this error only one trained investigator did all photographs.…”
Section: Shortcomingsmentioning
confidence: 90%
“…The performance and accuracy of the aforementioned methods with freehand 3-D ultrasound have not been evaluated in vivo , and the effect of the patient posture was not taken into account in above studies. It has been reported that the muscle balance and standing stability can be significantly influenced by body postures [32] , [33] . Chen et al [34] reported a preliminary study with four scoliosis patients to demonstrate the feasibility of measuring spine curvature based on a coronal view image formed using 3-D ultrasound imaging.…”
Section: Introductionmentioning
confidence: 99%